OPTIMIZING THE STRUCTURE OF AMPHIPHILIC INVERTIBLE POLYMERS (AIPs) MADE OF PEGS AND FATTY COMPOUND SEGMENTS TO OBTAIN A SINGLE CRITICAL MICELLE CONCENTRATION - Mohamed Dahrouch; Daniela Andrade; Susana Sanchez; Enzo Díaz; Stephane Mazières (Journal of the Chilean Chemical Society, 2020)
Amphiphilic biopolyesters containing hydrophilic segments (PEGs) and hydrophobic blocks (silicon fatty from a castor oil derivative) showed the ability to self-assembly in inverted micelles. Due to their capability to form also direct micelles, these biopolyesters could be classified as amphiphilic invertible polymers AIPs. The micellar concentrations CMC and ICMC corresponding to the direct and inverted micelles respectively precisely correlated with PEG length. The methodology used in this investigation allowed to determine the PEG length needed to obtain the adequate structural biopolyester able to self-assembly in direct and inverted micelles from a unique concentration. Inverted micelle diameters, determined by DLS analysis, increased as the molecular polarity of the biopolyesters decreased. No individual inverted micellar were observed by TEM technique due to the concentration change during the sample preparation, however micellar macromolecular aggregations were revealed.